TANTANGAN INDUSTRI KREATIF: INDUSTRI PERBUKUAN NASIONAL DAN PENGEMBANGAN MINAT BACA - Bambang Wasito Adi (Politeknik Negeri Media Kreatif, 2013)
This literature review on the creative industry aims to describe the creative economy, in particular on publishing subsector. Future economic trends that are being switched from the era of information technology to the creative economy become its own challenges for the book publishing world nationwide. Results of the review indicate that the direction of the world economy will switch to creative industries, industries that rely on the idea of creativity as the main capital development of a country. The challenge on the national book industry is how to develop reading interest that can be a deposit of human resource development.